2020
DOI: 10.1038/s41598-020-67823-8
|View full text |Cite
|
Sign up to set email alerts
|

A priori prediction of tumour response to neoadjuvant chemotherapy in breast cancer patients using quantitative CT and machine learning

Abstract: Response to neoadjuvant chemotherapy (nAc) has demonstrated a high correlation to survival in locally advanced breast cancer (LABC) patients. An early prediction of responsiveness to NAC could facilitate treatment adjustments on an individual patient basis that would be expected to improve treatment outcomes and patient survival. This study investigated, for the first time, the efficacy of quantitative computed tomography (qct) parametric imaging to characterize intra-tumour heterogeneity and its application i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…In their study, univariate parameter of homogeneity of HbO 2 map achieved the best 86% sensitivity, 89% specificity, and 88% accuracy from 37 LABC patients undergoing NAC. Recently, Moghadas-Dasterdji et al used quantitative textural features extracted from computerized tomography (CT) images for developing a priori response predictive model using different machine learning classification algorithms [ 56 ]. Their study included 72 LABC patients undergoing NAC and obtained the best classification results of 80% sensitivity, 88% specificity, 84% accuracy, and 0.89 AUC 0.632+ using an Adaboost decision tree (DT) classification algorithm [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, univariate parameter of homogeneity of HbO 2 map achieved the best 86% sensitivity, 89% specificity, and 88% accuracy from 37 LABC patients undergoing NAC. Recently, Moghadas-Dasterdji et al used quantitative textural features extracted from computerized tomography (CT) images for developing a priori response predictive model using different machine learning classification algorithms [ 56 ]. Their study included 72 LABC patients undergoing NAC and obtained the best classification results of 80% sensitivity, 88% specificity, 84% accuracy, and 0.89 AUC 0.632+ using an Adaboost decision tree (DT) classification algorithm [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Moghadas-Dasterdji et al used quantitative textural features extracted from computerized tomography (CT) images for developing a priori response predictive model using different machine learning classification algorithms [ 56 ]. Their study included 72 LABC patients undergoing NAC and obtained the best classification results of 80% sensitivity, 88% specificity, 84% accuracy, and 0.89 AUC 0.632+ using an Adaboost decision tree (DT) classification algorithm [ 56 ]. The response prediction results of these different imaging modalities are comparable with the results presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The response was classified using a modified RECIST score, using a combination of post-NAC imaging and histopathological specimen, which served as the gold standard [ 26 ]. Patients were classified into binary treatment response groups: responders and non-responders.…”
Section: Methodsmentioning
confidence: 99%
“…Even when studies revealed a large preponderance of specific clusters, such as a molecular taxonomy in which 74% of tumors falling into one of seven subtypes defined by specific gene fusions or mutations [ 20 ], patient stratification and outcome remain elusive [ 21 ]. Many challenges remain to integrate epidemiological studies with molecular investigations and clinical analyses to gain fundamental insights into how environmental, dietary, and lifestyle influences contribute to the development of PC, and thus a priori models selecting target genes involved in macroscopic functions could shed new light on this complex disease, as previous studies on different types of cancers have revealed [ 22 ].…”
Section: Introductionmentioning
confidence: 99%